Atrial Fibrillation in Hypertrophic Cardiomyopathy - G. A. Ignatenko; G. G. Taradin; N. T. Vatutin; A. A. Kaluga; Yu. D. Kostyamin (SINAPS LLC, 2021)
The current information about features of atrial fibrillation in patients with hypertrophic cardiomyopathy is presented in this review. The data about prevalence, pathogenesis and its various complications in these patients are disclosed. The article contains updated clinical recommendations of authoritative medical societies on the discussing problem. There is detailed discussion of risk factors of atrial fibrillation onset in setting of hypertrophic cardiomyopathy with demonstration of results of different studies concerning to investigation of relationship between risk factors and probability of the arrhythmia development. There is description of detection methods, clinical manifestations, and the course of atrial fibrillation in patients with hypertrophic cardiomyopathy. The contemporary literature data are presented regarding to the management of patients with atrial fibrillation with use of anticoagulants, antiarrhythmic drugs, indications for performing of radiofrequency ablation and results of studies concerning long-term efficacy of such procedure are demonstrated. The discussion on the management of the patients in cases of sinus rhythm restoration or maintenance failure is described.